A Cooperative Game Theoretical Approach to Risk Analysis, Using Network - Jun-ichi Takeshita,; Hiroaki Mohri, (Journal of Risk Analysis and Crisis Response, 2021)
The principal aim of this paper is to introduce the framework for a cooperative game theoretical approach to risk analysis using network structure. Probabilistic risk analysis (PRA) is a common methodology for evaluating risks associated with real-world network structure. Although there are numerous studies on PRA from a physical engineering perspective, Hausken (2002) noted that human behavior is a signifificant factor in estimating risk using PRA, and he integrated PRA and game theory. While his and related works focused on non-cooperative game theory, in some situations, such as chemical plants, cooperative structures are the norm. Therefore, we here provide a risk analysis method based on cooperative game theory, and especially so-called Shapley values.